Students Perceptions and Behavior in Responding to the Hoaxes of North Sumatra Election on TikTok - Friska Nabila Hanum; Frans Ananda Saragih; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research uses a qualitative method motivated by the rampant spread of political hoaxes through social media, especially TikTok, which is a popular platform for novice voters. The purpose of this study is to analyze the perceptions and behaviors of Medan State University students towards the North Sumatra Election hoax on TikTok. Data were obtained through an online survey using Google Form, observation, and thematic analysis. The data collected was then analyzed using the New Media Literacy theory by Jenkins et al. (2009). The results revealed that although students are quite adept at using digital media, they still have difficulty verifying political information. Their low political literacy makes them vulnerable to being exposed to and contributing to the spread of hoaxes.